Case study: Micro-learning and the sex industry. (1st January 2022) - Ahearne, Gemma
Abstract : This article interrogates the experience of introducing a micro-learning approach during the COVID pandemic and provides my reflections. It is argued that lectures delivered as micro-learning 'chunks' are preferable to traditional lectures in several ways, and that they facilitate rich and innovative seminar classes (Ahearne, 2021a; 2021b). The article concludes that some of the adaptations made during the pandemic should be retained afterwards if they enhance the student learning experience in that area of study.